O exército (...) é coisa do rebotalho da nação: recrutamento militar e manutenção da ordem no Brasil (1840-1852) - Meira, Lis de Araújo (2018)
The present study, linked to the History and Regionalities, line of the Post-Graduation Program in History, at the Federal University of Paraíba, has as its object military recruitment in the nineteenth century, which presented itself as a process that caused a great deal of restlessness in of the provinces of the Brazilian Empire. In our research, we observed the discomfort caused by recruitment, which happened, in general, in a coercive way, and for this reason we make a distinction between forced and voluntary recruitment. The present study is based on several documents, including correspondence between authorities, reports of provincial presidents and newspapers that circulated in nineteenth-century Brazil, we observed recruitment as an instrument of control of a nation-state under construction. We also analyze the state control, the military organization, the maintenance of the order and the networks of privileges prevailing of that society, under the theoretical reference of the political cultures. The military recruitment was more than a simple instrument to fill the ranks of the Brazilian Army, it was part of the political game that involved several social categories. We analyze the practices surrounding recruitment in this period and how this process served as an instrument of control for those in power and was used as a weapon in the pursuit of political opponents. We consider the political parties that carried out politics in nineteenth century in Brazil, conservative and liberal politicians, and how both used recruitments to intimidate their opponents. The present study starts from the national sphere for the provinces sphere, we choose Paraíba to detail the mechanisms that guided military recruitment. In addition, the forced enlistment of men for the Brazilian Army was also an instrument of control of poor free individuals who did not conform to the social molds imposed by the elites.